2017 National Turfgrass Evaluation Program Perennial Ryegrass Test: 2018 Data - Mingying Xiang; Jack Fry (Kansas Agricultural Experiment Station Research Reports, 2019)
More than 100 entries of perennial ryegrass were evaluated in the perennial ryegrass National Turfgrass Evaluation Program (NTEP) study in Manhattan, KS, in 2018. A broad variation occurred among entries. Several entries consistently ranked in the top 10 in quality from month to month.
Keywords: NTEP; perennial ryegrass; quality